Positive and negative viral associations in patients with acute respiratory tract infections in primary care: the ECOVIR study - Petat, Hortense; Schuers, Matthieu; Marguet, Christophe; Humbert, Xavier; Le Bas, François; Rabiaza, Andry; Corbet, Sandrine; Leterrier, Bryce; Vabret, Astrid; Ar Gouilh, Meriadeg (Frontiers in Public Health, 2023)
Introduction Acute respiratory infections (ARIs) are the most common viral infections cared in primary care settings. The identification of causal viruses is still not available in routine practice. Although new strategies of prevention will happen, the knowledge on relationships between respiratory viruses remain limited. Material and Methods ECOVIR was a multicentric prospective study in primary care, during two pre-pandemic seasons (2018-2019 and 2019-2020). The patients attending their General practitioner (GP) with ARIs were included, without selecting age or clinical conditions. Viruses were detected on nasal swabs samples by a multiplex Polymerase Chain Reaction test focused on 17 viruses (Respiratory Syncytial Virus-A (RSV-A), RSV-B, Rhinovirus/Enterovirus (HRV), human Metapneumovirus (hMPV), Adenovirus (ADV), Coronaviruses (CoV) HKU1, NL63, 229E, OC43, Influenza virus (H1 and H3 subtypes), Influenza virus B, Para-Influenza viruses (PIV) 1-4, Bocavirus (BoV)). Results Among the 668 analyzed samples, 66% were positive for at least one virus, of which 7.9% were viral codetections. The viral detection was negatively associated with the age of patients. BoV, ADV and HRV occurred more significantly in younger patients than that did the other viruses (p<0.05). Codetections were significantly associated with RSV, HRV, BoV, hMPV and ADV, and not associated with influenza viruses, CoV and PIVs. HRV and influenza viruses were negatively associated with all the viruses. Conversely, a positive association was found between ADV and BoV, and between PIVs and BoV. Conclusion Our study provides additional information on the relationships between respiratory viruses, which however remained limited in primary care.